Metal Resistance and Tolerance to Temperature Stress of Plants Inoculated with Endophyte Cylindrocarpon Magnusianum Wollenw. - Bukharina, Irina; Islamova, Nadezhda (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Inoculations of Cylindrocarpon magnusianum Wollenw. endotrophic micromycete and inoculant reactions to the action of heavy metal salts in the substrate (for Solánum lycopérsicum L.) and the effect of high temperatures (for Poa pratensis L.) were studied. The experimental design included inoculation with the culture of the fungus and populations of the fungus adapted to the action of the stress factor. Then, inoculated plants were grown under control conditions and on substrates with the addition of different concentrations of zinc, copper, lead and chromium salts, or under conditions of temperature stress.We have not revealed a stimulating effect that increases the resistance of plants to the action of salts of heavy metals during inoculation of plants with a control population of the fungus. When using non-biogenic chemical elements, adaptive plant reactions associated with the content of photosynthetic pigments in the leaves and the formation of plant biomass were significantly manifested when plants were inoculated with adapted populations of the fungus C. magnusianum on substrates with the addition of chromium and lead salts. Under these conditions, a more intense development of fungal infection in plant roots was observed, in contrast to the use of the control fungal population. High temperatures led to significant changes in the content of ascorbic acid, photosynthetic pigments in the leaves, the distribution of plastic material between the aerial part and the root system of plants in inoculated plants. These reactions are adaptive. The facts obtained indicate the most effective partnership of the fungus C. magnusianum and the root system of plants under conditions extreme for plant life.